Analysis of the Best Interest Principle for Children in Custody Disputes Between Biological Mothers and Foster Mothers - Layyinatusy Syifa; Fakhrurrazi M. Yunus; Riza Afrian Mustaqim (QURU’: Journal of Family Law and Culture, 2025)
Custody disputes between biological and adoptive mothers often pose legal dilemmas as they involve both biological and social aspects, particularly in determining who has the stronger claim to raise the child. This study aims to examine and analyse the judges' reasoning at the first instance, appellate, and cassation levels, with reference to the application of the principle of the best interests of the child. Using a normative juridical method and a case study approach, the findings reveal that at the first instance and cassation levels, the principle of the best interests of the child was not comprehensively applied. The panel of judges focused primarily on formal provisions set out in the legislation, thereby neglecting the factual circumstances relating to the child's well-being. In contrast, at the appellate level, the Aceh Sharia Court adopted a different approach by prioritising the best interests of the child, reflecting a more holistic and child-centred perspective. These findings conclude that the application of the best interests of the child principle greatly depends on the interpretation of judges at each level of the judiciary. Therefore, a deep understanding of this principle is essential to ensure that legal decisions not only fulfil formal legal aspects but also have a positive impact on the child's future.